Interindividual epigenetic variation in ABCB1 promoter and its relationship with ABCB1 expression and function in healthy Chinese subjects - Wu, Lan‐Xiang; Wen, Chun‐Jie; Li, Ying; Zhang, Xue; Shao, Ying‐Ying; Yang, Zhu; Zhou, Hong‐Hao (British journal of clinical pharmacology, 2015)
Aim Interindividual epigenetic variation is likely to be an important mechanism contributing to the interindividual variability in the expression and function of ATP‐binding cassette, sub‐family B, member 1 (ABCB1). The aim of the present study was to explore the effect of interindividual epigenetic variability in the ABCB1 promoter on ABCB1 expression and function in healthy Chinese subjects. Methods Using bisulfite sequencing polymerase chain reaction (PCR) and chromatin immunoprecipitation assays, the DNA methylation and histone acetylation status of the ABCB1 promoter in stool DNA and exfoliated colonic epithelial cells of 157 healthy Chinese male volunteers was analysed. ABCB1 mRNA levels in colonic epithelial cells were detected by real‐time PCR. The digoxin pharmacokinetics in subjects with different epigenetic profiles was investigated after a single oral administration of digoxin (0.5 mg). Results The methylation levels of ABCB1 promoter in stool DNA showed a significant interindividual variation, from 0.84% to 18.05%. A high methylation level of the ABCB1 promoter was closely related to the low levels of acetylated histone H3 and ABCB1 mRNA expression. In the high methylation group, the area under the concentration–time curves (AUC(0–4 h) and AUC(0–10 h)) of digoxin was increased by 19% [95% confidence interval (CI) 10%, 31%; P = 0.024] and 13% (95% CI 8%, 26%; P = 0.026), respectively, and the peak concentration (Cmax) of digoxin was increased by 30% (95% CI 12%, 41%; P = 0.021) compared with the low methylation group. Conclusions The epigenetic modifications of the ABCB1 promoter show high interindividual variability in healthy Chinese subjects, and are closely related to the interindividual variation in ABCB1 mRNA expression and digoxin 0–4 h plasma concentrations in vivo.